Malic enzyme 2 as a potential therapeutic drug target for cancer. Issue 11 (29th August 2018) - Sarfraz, Iqra; Rasul, Azhar; Hussain, Ghulam; Hussain, Syed Makhdoom; Ahmad, Matloob; Nageen, Bushra; Jabeen, Farhat; Selamoglu, Zeliha; Ali, Muhammad
Abstract: Reprogrammed metabolic profile is a biochemical fingerprint of cancerous cells, which represents one of the "hallmarks of cancer." The aberrant expression pattern of enzymatic machineries orchestrates metabolic activities into a platform that ultimately promotes cellular growth, survival, and proliferation. The NADP(+)‐dependent mitochondrial malic enzyme 2 (ME2) has been widely appreciated due to its function as a provider of pyruvate and reducing power to the cell for biosynthesis of fatty acids and nucleotides along with maintenance of redox balance. Multiple lines of evidences have indicated that ME2 is a bonafide therapeutic target and novel biomarker which plays critical role during tumorigenesis. The objective of this review is to provide an update on the cancer‐specific role of ME2 in order to explore its potential for therapeutic opportunities. Furthermore, we have discussed the potential of genetic and pharmacological inhibitors of ME2 in the light of previous research work for therapeutic advancements in cancer treatment. It is contemplated that additional investigations should focus on the use of ME2 inhibitors in combinational therapies as rational combinations of metabolic inhibitors and chemotherapy may have the ability to cure cancer. © 2018 IUBMB Life, 70(11):1076–1083, 2018